Cross-cultural adaptation and psychometric properties of the Brazilian-Portuguese version of the Quality of Prenatal Care Questionnaire (QPCQ) - Rodrigo Dias Nunes; Gabriel Cremona Parma; Andressa Cardoso de Campos; Paula Locatelli; Jefferson Traebert (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To translate and to observe the psychometric measures of the Brazilian version of the Quality of Prenatal Care Questionnaire. METHODS The translation protocol followed the standards of the International Society for Pharmacoeconomics and Outcomes Research. Descriptive statistics were performed to identify characteristics of 280 literate postpartum women in a public hospital. We examined the internal consistency using Cronbach's alfa. To determine the test-retest reproducibility and the instrument's stability, we performed the intraclass correlation coefficient and Bland and Altman plot between two applications. We investigated the item's properties using the item response theory. RESULTS The overall Cronbach's alpha index was 0.975. The intraclass correlation coefficient was 0.995 (95%CI 0.993-0.996) and a uniform distribution was visualized at the Bland and Altman plot. The item response theory identified the discriminatory power and the difficulty level of the instrument and of each item. The instrument showed acute angulation of the expected total score, and good concentrate information and good standard error curves, preserving the latent construct and its original items. CONCLUSIONS This analysis concluded that the Brazilian version of the Quality of Prenatal Care Questionnaire is a high-quality, reliable and valid questionnaire to determine the quality of prenatal care among Brazilian women. The questionnaire is suitable for the cultural context represented.